Pembinaan Warga Gereja sebagai Landasan Penguatan Pelayanan Kristen - Remita Nian Permata Zendrato; Johanes GB Panjaitan; Megawati Manullang (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2025)
The development of church members serves as a crucial foundation for strengthening Christian ministry. This effort aims to nurture a congregation that is mature in faith, character, and service, enabling them to actively introduce Christ to the world. The church faces significant challenges in increasing congregational participation, particularly among the younger generation, who are often more focused on digital life. Therefore, continuous training is essential to fortify the faith of the congregation and prepare them to engage in Christian ministry. Effective training methods include fellowship, Bible teaching, mentoring, and social service. This development not only strengthens relationships among congregation members but also equips them to serve in various aspects of life. Through ongoing development, the church will produce a congregation that is strong in faith, active in ministry, and ready to face the challenges of the times.